Mechanism of Financing the System of Long-Term Nursing in Russia: Current Standing and Prospects - D. V. Nekipelova (Вестник Российского экономического университета имени Г. В. Плеханова, 2024)
The system of long-term nursing is an important element of the system of social welfare, which gives an opportunity to create necessary conditions for worthy life of elderly people with restrictions and disabled ones. At the same time it can decrease the burden on the Public Health System in rendering in-patient and out-patient services to these people and on households in arranging lasting care in the form of unpaid work of relatives and in the form of expenses on medication and technical means of rehabilitation. In this way relatives who have to do nursing, can keep their employment and realize themselves in society and the family will not lose incomes. In view of the increasing trend of populating aging and of growing share of people older than the retirement age establishing and developing the system of long-term nursing is a very serious goal. However, it will need a clear and stable source of financing. In Russia the system of long-term nursing has been developing as a pilot project only for 5 years and results of this work are extremely important. The article appraised the effective mechanism of financing the system of long-term nursing for elderly people and disabled ones, analyzed different variants of financing long-term nursing systems in world practice and provided feasible potential of their introduction in home practice.